Information Security Management in the Context of Strategic Changes - Elena RYABOVA; Elena ALEKSANDROVA; Olga FILIPPOVA (Communications of International Proceedings, 2022)
Effective management is now a key requirement imposed on enterprises by the market. Constant changes, primarily in the economic environment, lead to a continuous search and improvement of business strategy and tactics. On the other hand, in modern conditions it is impossible to achieve effective business without the use of information technologies, which, in turn, are rapidly and intensively developing precisely under the influence of the strategic and tactical tasks facing the business. The article presents the concept of change management, discusses the issues of its theoretical and practical application in the field of information security, highlights the specifics of the process of developing and implementing an information security strategy in the context of strategic changes.
Keywords: Information Security; Management; Strategy; Changes.